Towards an Explanatory Taxonomy of Adolescent Delinquents: Identifying Several Social-Psychological Profiles - Brennan, Tim (Journal of quantitative criminology, 2008)
Taxonomic structure is examined in two large samples of delinquent youth in a domain of socio-psychological and personality factors. This paper offers a partial empirical test of the overlapping theoretical taxonomies of Moffitt (Pshycol Rev 100:674–701, 1993), Lykken (The antisocial personalities, 1995) and Mealey (1995). The first sample consisted of juvenile offenders ( n = 1,572) from three state systems. Multiple cluster analysis methods were applied (Wards method, standard K-means, bootstrapped K-means and a semi-supervised pattern recognition technique). Core or exemplar cases were identified by means of a voting procedure. Seven clusters recurrently emerged across replications. While clear analogues of Moffitt’s two main categories were found, several additional stable subtypes emerged that were clearly reminiscent of Lykken’s sociopathic, neurotic-internalizing and “normal” types. However, boundaries between types were fuzzy and unstable, and many unclassified cases existed. Internal validation was assessed by cross-method verification. External validation assessed type differentiation on several delinquent behaviors. Finally, generalizability was assessed by repeating the clustering on a large replication sample ( n = 1,453) from another state. Six of the seven initial types re-emerged.